Development of Web-Based Digital System Learning Media - Togas, Peggy V.; Naharia, Orbanus; Manggopa, Hiskia; Rompas, Parabelem D.T; Oroh, Rolly (AIBPM Publisher, 2021)
In classroom learning, students frequently face challenges to understand the material since the learning media deviates from the subject content. The media usage as an intermediary for delivering information makes it more varied, easy to understand, and interactive. Utilizing web-based learning media promises the independence of time and place and helps the learning process. This study aims to develop a web-based digital system learning media that is feasible and useful. The study uses the waterfall model software development method, namely the Multimedia Development Life Cycle (MDLC). The findings indicate that the web-based digital system learning media is feasible and useful in the learning process.